Designing destination image: Integrating hotel and MICE functions to strengthen a coastal city's global competitiveness - Nova Puspita Anggraini; Ahmad Mumtaz; Lely Mustika (The Journal of City: Branding and Authenticity, 2026)
Background: The development of the Ancol coastal area as an integrated tourism and business destination still faces limitations in the capacity of MICE (Meetings, Incentives, Conferences, and Exhibitions) facilities and internationally standardized hotel accommodations. This design project aims to develop a five-star convention hotel in the Pantai Indah area of Ancol that integrates hotel and convention functions while responding to the characteristics of the coastal environment through a modern-contemporary architectural approach. Methods: The design method involves literature study, site analysis, benchmarking, and the formulation of spatial, structural, and building-system concepts. Findings: The results indicate that the main site issues include tidal flooding, high humidity, noise, and exposure to sea winds, while the greatest potential lies in its orientation toward views of the Java Sea and strong accessibility. Design strategies are implemented through elevation of the ground floor, clear zoning of public–semi-public–private areas, optimization of natural lighting and ventilation, integrated HVAC systems, and the use of corrosion-resistant materials combined with green-building principles. The final design produces a convention hotel that meets five-star service standards, supports MICE activities effectively, offers luxurious and comfortable spatial experiences, and strengthens Ancol’s image as an international-class business tourism destination. Conclusion: This study concludes that the proposed contemporary convention hotel integrates functional efficiency, coastal environmental responsiveness, and a strong destination identity, positioning it as a resilient MICE facility that supports tourism development and city branding in Ancol. Novelty/Originality of this article: This study proposes a coastal-responsive convention hotel design that integrates environmental adaptation with destination identity to strengthen Ancol's city branding as an international MICE tourism destination.